(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Purpose. To compare the efficacy of ranibizumab and aflibercept treatment of patients with choroidal neovascularization (CNV) in pathologic myopia. Material and Methods. This was a comparative, uncontrolled, prospective cohort study, enrolling 96 pathologic myopic eyes (93 patients) with subretinal neovascularization. Results. 65 eyes (63 patients) were treated with 0.5 mg intravitreal ranibizumab; 31 eyes (30 patients) were treated by 2 mg intravitreal aflibercept. The baseline mean visual acuity was 0.2 and 0.21 in the intravitreal ranibizumab (IVR) and intravitreal aflibercept (IVA) groups, respectively. At 12 months, the mean visual acuity was 0.4 and 0.37 for the IVR and IVA groups, respectively. The mean CRT at baseline was 314.6 µm and 276.5 µm for the IVR and IVA groups, respectively. At 12 months, the mean CRT was 226.7 µm (р = 0.000) and 224.3 µm (р = 0.000) for the IVR and IVA groups, respectively. The mean number of injections in the IVR and IVA groups was 2.3 (0.9) and 2.6 (0.9), respectively. No statistically significant difference was noted in the number of injections between groups (р = 0.15). Conclusions. Both ranibisumab and aflibercept were found to improve the visual acuity in pathologic myopic patients with CNV with no statistically significant difference in the number of intravitreal injections.